Management of Financing in Community Learning Activity Centers - Nurfitriani Nurfitriani; Eka Yudhyani; Catur Kumala Dewi; Rina Masithoh Haryadi; Sunarto Sunarto (Universitas Negeri Semarang, 2024)
The Center for Teaching and Learning Activities (PKBM) is one of the non-formal educational institutions that has a strategic role in improving the quality of human resources through various learning programs. PKBM provides a variety of educational services such as equality education, skills training, and various kinds of community empowerment programs. For sustainability and effectiveness, the program is highly dependent on effective and efficient financing management. The purpose of the study is to describe the characteristics of sources and Revenue Budget Plans (RAP) in PKBM Karya Bhakti Punung, to describe the characteristics of financial realization and accountability in PKBM Karya Bhakti Punung. The method used in this study is data description with an ethnographic approach. Data collection used interview techniques with selected resource persons. The results obtained from this study are known if the sources of funds contained in PKBM Karya Bhakti are obtained from the government, namely from the Director General of PNFI (Indonesia Non-Formal Education), the East Java Provincial Education Office, and the Pacitan Regency Education Office, in addition to that the sources of funds are obtained from independent or independent institutions and businesses from PKBM itself. By diversifying funding sources and optimizing the use of funds, PKBM can reduce dependence on one source of funding, thereby increasing operational stability and financial sustainability. Good management also allows greater access to resources, which can be used to improve the quality of education and services, as well as develop more relevant and innovative programs and curricula. The active participation of the community in the financing management process will strengthen the relationship between PKBM and its community, as well as encourage greater support. Seeing this, additional funds are needed for PKBM so that educational activities can run as well as possible.